1999
DOI: 10.1111/j.1468-3083.1999.tb01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous Aspergillosis in a patient with acquired inmunodeficiency syndrome

Abstract: 6] Purtilo DT, Lindei syndrome (AIDS) J, Volsky DJ. Clin Lab Med Acquired 1986;6:3 immune -26. Letters deficiency [7] Rubio FA, Robayna C, Herranz P, et al. Leishmaniasis presenting as a psoriasiform eruption in AIDS. Br J Dematol 1997; 1363792-806, [El Hell E, Hodgson C. The uptake of 3H-thymidine by epidermal cells in normal and psoriatic subjects. Br J Dermatol 1966:78:262-268.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Risk factors for invasive aspergillosis include neutropenia, glucocorticoid therapy, advanced acquired immunodeficiency syndrome, chronic granulomatous disease, hematopoietic stem cell or solid-organ transplantation (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Aspergillus infections are also common in premature and newborn infants hospitalized in intensive care according to the literature (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for invasive aspergillosis include neutropenia, glucocorticoid therapy, advanced acquired immunodeficiency syndrome, chronic granulomatous disease, hematopoietic stem cell or solid-organ transplantation (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Aspergillus infections are also common in premature and newborn infants hospitalized in intensive care according to the literature (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Invasive aspergillosis less frequently involves the sinuses, orbit, eye, heart or other viscera 8,13,17,19,25 . Primary cutaneous lesions 2,14 and isolated tracheobronchitis 23 have been reported. A previous study reported aspergillosis diagnosed between 10 and 26 months following onset of AIDS; despite anti-fungal therapy, these patients died within two to four months 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Primary infections caused by direct physical inoculation were rare 2–5 . Recently, however, primary cutaneous aspergillosis seems to be an emerging infection in immunocompromised patients 6–8 and rare in subjects with normal immune status 9,10 …”
Section: Introductionmentioning
confidence: 99%